IMPLEMENTATION OF FOREST AND LAND FIRE DISASTER MITIGATION POLICIES IN LIMA PULUH KOTA - Kevin Mandaila Putra; Rahmadani Yusran (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Forest and land fires (karhutla) in Lima Puluh Kota represent a recurrent threat with severe environmental, social, and economic impacts. Although a regulatory framework exists under Regent Regulation No. 38 of 2018, the implementation of mitigation policies in the field continues to face structural obstacles. This study aims to critically analyze the implementation of forest and land fire disaster mitigation policies and identify the key factors determining their success. Utilizing a descriptive qualitative approach, data were gathered through observations, documentation, and in-depth interviews with seven key informants selected via purposive sampling. Data were interactively analyzed through data reduction, data display, and conclusion drawing. The findings indicate that policy implementation is fairly effective but has not reached optimal performance. This status is evidenced by specific operational indicators, including low patrol frequency (once a month), uneven outreach coverage due to budget constraints, and inconsistent personnel competency enhancement. The primary structural barriers include severe personnel shortages (only 13 Brigade members), inadequate infrastructure and firebreaks, and the persistent practice of traditional land clearing by burning. Analytically, the study concludes that mitigation success is fundamentally constrained by institutional resource limitations. Policy implications highlight the urgent need for local governments to strengthen operational funding, expand technical firebreak construction, and shift community engagement from passive advisories to active farmer-group empowerment.